Shaping New Englands: Puritan clergymen in seventeenth-century England and New England - Bremer, Francis J. (Twayne's United States authors series, 1994)
"There is no questioning the importance of colonial authors - particularly the Puritan leaders of the seventeenth century - in American history and literature. The work of such men as John Cotton, Thomas Hooker, Richard Mather, and Roger Williams, the "shining lights" who sought to shape a model society, provided much of the fundamental structure upon which the new colonies were built. Frustrated in their reformation efforts in old England, these English men, voicing English concerns for English audiences, sought to implement their plan in the new England. Thus, as author Francis J. Bremer chronicles, they were indeed "shaping new Englands."" "In this welcome study, Bremer provides a teeming survey of virtually every seventeenth-century Puritan clerical writer of significance, studying not only the books, but also sermon notes and unpublished manuscripts. In so doing, he provides an astoundingly rich body of work and a truly unique perspective. Bremer's thoughtful approach distills the unity in outlook among these preachers - without abandoning the diversity that existed in tone, practice, and belief. Carefully reviewing the methods and assumptions of many preceding scholars, he adventures into new territories and even back toward once discarded avenues. No aspect of the Puritan movement is left unexamined as Bremer illuminates much more than merely subject matter and viewpoint. Beginning with a clear and thoughtful introduction that defines, among other details, the Anglo-American context in which this story is told, he proceeds to the events that gave rise to the Puritan movement; the Puritan style; writings of theology and piety, views on polity and social matters; and, finally, the changes wrought in the new Englands - and how the writings changed in response."--BOOK JACKET